(untitled) - Keenan, Denis (Harlow, 2005)
The market-leading text for service courses on introductory business law. "Business Law 7th edition" provides a clear, jargon-free and easy to understand text for students new to law. Comprehensive coverage and well illustrated by cases, diagrams, specimen documents and questions. The text provides an excellent teaching resource for business law focusing on introductory aspects of English law and the English legal system; the law relating to business organisations, namely sole traders, partnerships and companies; legal aspects of business transactions, covering contract, tort, sale and supply of goods, consumer law and criminal liability in the context of business; and the law relating to employment.
Keywords: Business law,Private law; England,Wales